Using Ozone for Integrated Pest Management in Viticulture - Bhadra, Rumela (My University, 2016)
The common grape, Vitis vinifera, is native to the Mediterranean region, central Europe, and southwestern Asia—from Morocco and Portugal to southern Germany and northern Iran. There are currently 5,000 to 10,000 known varieties of Vitis vinifera, although only a small proportion are of commercial significance for wine (about 500 to 1,000 known subtypes), including the popular Cabernet Sauvignon, Chardonnay, Merlot, Pinot Noir, and Riesling. California's Central Valley is the main grape-growing region in the U.S., and there has been dramatic growth in the wine industry throughout the Midwest. However, while the Central Valley has ideal climate conditions for growing vinifera varieties—including ample sunshine, dry and windy summers, mild winters, and gentle slopes—the Midwest is known for its long, cold winters and hot, humid summers. In the Midwest, vines often suffer bud and stalk injury during the harsh winters, and the humid summers can increase the risk of pest-related diseases.
Citation: Bhadra, R. 2015. Using Ozone for Integrated Pest Management in Viticulture. Resource Magazine, July/August Issue: 22(4): 15-17. ASABE, St. Joseph, MI.
Keywords: Viticulture; Enology; Ozone; IPM